MECHANISMS OF HORMONE-DRIVEN TRANSFORMATION OF NK CELLS IN PREGNANCY - Shirshev, S.V.; Nekrasova, I.V.; Gorbunova, O.L.; Orlova, E.G.; Maslennikova, I.L. (Perm Federal Research Centre Journal, 2017)
The influence of reproductive hormones (HCG, estriol, kisspeptin, leptin, ghrelin) on phenotypic characteristics, cytokine production and the level of lytic activity of natural killer (NK) cells was studied. The role of miRNAs in the hormonal mechanisms of the formation of regulatory and cytotoxic subpopulations of NK cells during pregnancy was investigated.It was established that the reproductive hormones shift the balance of NK cells from cytotoxic subpopulation to the regulatory one. Herewith, the expression of the inhibitory molecule NKG2A and L-selectin was increased. The hormones at concentrations, corresponding to their levels during pregnancy, modulate cytokine spectrum, which is characteristic of regulatory NK3 subpopulation. The revealed action of hormones, manifested in the decrease of cytotoxic potential in the separated NK cells, in some cases was realized through the regulation of the level of the specific microRNAs.As a result of this work new physiological mechanisms of endocrine control of NK cells of the mother’s immune system were identified, which could be implemented in different periods of pregnancy.